In silico evaluation of Lipl32 peptides for antigen candidates in leptospirosis diagnostic - Esteban, Micaela; Saraullo, Vanina Rosa; Madero, Agustin; Hamer, Micaela; Sanchez, Maria Cristina; Brihuega, Bibiana Felicitas; Martinez, Mara Leila (International Leptospirosis Society, 2024)
Poster